2014
DOI: 10.1016/j.agee.2014.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of timing and frequency of mowing on the threatened scarce large blue butterfly – A fine-scale experiment

Abstract: As part of a major transformation of the EU agriculture in the last few decades, traditional land-use types disappeared due to either intensification or abandonment. Grasslands are highly affected in this process and are consequently among the most threatened semi-natural habitats in Europe.However, experimental evidence is scarce on the effects of management types on biodiversity.Moreover, management types need to be feasible within the recently changed socio-economic circumstances in Hungary. We investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
2
24
0
Order By: Relevance
“…Some studies have shown that most fauna may be removed when the grass is harvested but the regrowth is rapidly recolonized by species that have short life cycles and high reproductive rates (Purvis and Curry , Körösi et al. ). Mowing once a year in our study provides arthropod communities with a long recovery period, which may contribute to the higher diversity under mowing than grazing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that most fauna may be removed when the grass is harvested but the regrowth is rapidly recolonized by species that have short life cycles and high reproductive rates (Purvis and Curry , Körösi et al. ). Mowing once a year in our study provides arthropod communities with a long recovery period, which may contribute to the higher diversity under mowing than grazing.…”
Section: Discussionmentioning
confidence: 99%
“…It also affects soil animal community negatively/positively depending on the timing and frequency of mowing (Körösi et al. ). Enclosure by fencing, which means ungrazed or under rest, is commonly used as a main means of restoring degraded grassland (Yan and Lu ).…”
Section: Introductionmentioning
confidence: 99%
“…Partial mowing, a management practice that enhances P . nausithous densities, is beneficial for ant assemblages exploited by butterflies [87] and seems to be an effective measure for maintaining Phengaris butterflies [8789] (but see [90]) and overall diversity of invertebrates [91]. …”
Section: Discussionmentioning
confidence: 99%
“…spring or autumn mowing occupied an intermediate position in terms of the above parameters (Szépligeti et al 2016). A keystone species of nature conservation, Phengaris teleius (Bergsträsser) butterfly and its host plant, Sanguisorba officinalis, showed the highest density on the patch mown once a year in autumn (Kőrösi et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Since 1990, due to economic considerations, once-a-year (MayJune) mowing became the typical way of management and abandonment became widespread as well (Babai et al 2015). Around 2000, mowing once-a-year in August-September was introduced on some valuable grasslands due to the prescriptions of the national park administration to protect butterfly species, such as Maculinea species (Kőrösi et al 2014). To understand the effect of the above listed management regimes on the plant and animal communities of meadows, Őrség National Park Directorate launched an experiment on four of its own meadows in 2007.…”
Section: Introductionmentioning
confidence: 99%